Enhanced bandwidth nonlinear resonance electromagnetic human motion energy harvester using magnetic-springs and ferrofluid - Li, Chungfang; Wu, Shuai; Luk, Patrick Chi-Kwong; Gu, Min; Jiao, Zongxia (IEEE, 2019)
An enhanced bandwidth nonlinear resonant electromagnetic energy harvester has been designed to harness low frequency energy from basic human motion. Some vertical stacked cylindrical permanent magnets (PMs) constitute the inertial mass of the proposed harvester, which is suspended axially by two magnetic-springs and circumferentially by ferrofluid within a carbon fiber tube. In order to widen the frequency band and improve harvesting efficiency, two PMs are respectively fixed on the two end caps of the carbon fiber tube, so as to form two magnetic-springs with variable stiffness by cooperating with the PM stack. The self-assembled ferrofluid around the PM stack acts as its bearing system to minimize any friction during its movement. Copper wire are wrapped outside the tube to form the armature winding. The stiffness characteristic of the magnetic-springs and the optimum equilibrium position and number of windings have been determined by finite element method (FEM) analysis. As a proof of concept, a portable prototype of the proposed energy harvester that weighs 110g and with a volume of only 37.7cm $^3$ is fabricated. A series of experiments are carried out and the results show that the frequency band of the harvester becomes wider as the external vibration intensity increases. In addition, the effectiveness of ferrofluid in reducing friction is demonstrated under walking and running conditions. Without ferrofluid, the maximum average outputs are 10.15 mW and 32.53 mW respectively for walking and running. With ferrofluid, the maximum outputs are 17.72 mW and 54.61 mW, representing an increase of 74.58% and 67.88%, respectively. Furthermore, the prototype exhibits an average power density of 1.45 mW/cm $^3$ during running motions, which compares favorably with existing harvesters used in low power wearable devices.
Keywords: Nonlinear resonance; vibration energy harvester; human motion; magnetic-spring; ferrofluid; smart fluid